Perluasan Pasar dan Model Kemitraan Beras Organik di Kecamatan Uepai Kabupaten Konawe - Yusria, Wa Ode; Rosmawaty, Rosmawaty; Batoa, Hartina (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2017)
The aim of this study was to measure the ability of organic rice products (competitiveness) in accessing markets (Market Share). The research used market share analysis for answering the research objective. The research results showed that the ability of product (organic rice) based on variant analysis is influenced not only by price but also non-price factors. The percentage value of the price factor (65.06%) was greater than the non-price factor (34.94%). The price factor was influenced by the product’s competitiveness and consumer purchasing power. While the non-price factor was affected by distribution or products salesman and products that were marketed.